(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
اُستخلصت المواد الفعالة الناتجة عن نمو جراثيم الزائفة الزنجارية Pseudomonas aeruginosa المعزولة من مصادر مختلفة بالمحل العضوي إيتيل أسيتات. أظهرت دراسة الفعالية الصادة للمستخلصات الجرثومية تجاه الجراثيم الممرضة المعزولة من عينات مرضية مأخوذة من مختبر مستشفى الأسد الجامعي في اللاذقية فضلاً عن عزلتين من مياه بحرية بطريقة الانتشار بوساطة الأقراص أن المستخلصات الجرثومية تمتلك فعالية صادة في الجراثيم السلبية غرام (Serratia marcescens, Proteus vulgaris, Pseudomonas cepacia) والإيجابية غرام (Streptococcus pneumoniae, Streptococcus faecalis, Streptococcus sp., Staphylococcus aureus, Staphylococcus albus, Staphylococcus epidermidis) والمجموعة الأخيرة كانت أكثر حساسية لهذه المستخلصات الجرثومية. وهكذا يبدو أن منتجات جراثيم Pseudomonas aeruginosa قد تكون أحد المصادر الممكنة للمركبات الصادة الطبيعية في الجراثيم الممرضة في المستقبل. Cultures of Pseudomonas aeruginosa ,which were isolated from different sources, were extracted with ethyl acetate (EtOAc). Results study the effect of extracts against pathogenic bacteria, which were isolated from Al-Assad hospital laboratory in Lattakia and two isolates from sea water, with disk diffusion method showed antibacterial activity against Gram-negative bacteria (Serratia marcescens, Proteus vulgaris, Pseudomonas cepacia) and Gram-positive bacteria (Streptococcus pneumoniae, Streptococcus faecalis, Streptococcus sp., Staphylococcus aureus, Staphylococcus albus, Staphylococcus epidermidis) the last one were the most susceptible. Depending on these results, we can say that the extracts of Pseudomonas aeruginosa are expected to be potential resources of natural antibiotic products against pathogenic bacteria in the future.